2022
DOI: 10.1177/02698811221095528
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like effect of tofisopam in mice: A behavioural, molecular docking and MD simulation study

Abstract: Background: Depression is a disease that affects millions of people worldwide, and the discovery and development of effective and safe antidepressant drugs is one of the important topics of psychopharmacology. Objectives: In this study, it was aimed to investigate the antidepressant-like activity potential of tofisopam, an anxiolytic drug with 2,3-benzodiazepine structure, and to elucidate the pharmacological mechanisms mediating this effect. Methods: The antidepressant-like activity of tofisopam was investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 80 publications
(110 reference statements)
1
3
0
Order By: Relevance
“…All MDS were carried out for 100 ns to analyze the stability of the identified hits from the in vitro with docking results. System setup preparation, MDS, and interaction analysis calculations were carried out according to the same procedure from previous studies. , …”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…All MDS were carried out for 100 ns to analyze the stability of the identified hits from the in vitro with docking results. System setup preparation, MDS, and interaction analysis calculations were carried out according to the same procedure from previous studies. , …”
Section: Methodssupporting
confidence: 90%
“…System setup preparation, MDS, and interaction analysis calculations were carried out according to the same procedure from previous studies. 24 , 40 …”
Section: Methodsmentioning
confidence: 99%
“…Molecular dynamic simulations included calculations of radius of gyration (Rg), root‐mean‐square fluctuation (RMSF), and root‐mean‐square deviation (RMSD) via the Desmond application. [ 29,49,50 ]…”
Section: Methodsmentioning
confidence: 99%
“…In this study, MDS for 100 ns was carried out to ensure the stability of the identified hits from the docking results, and then the interaction types and strengths were analyzed. The method was applied similarly to our previous studies [14,[22][23][24]. Using the standard force field (OPLS3e) of Schrodinger's Suite with a transferable intermolecular potential with 3 points (TIP3P) water model followed by energy minimization of the complex in the Desmond application [25].…”
Section: Molecular Dynamics Study (Mds)mentioning
confidence: 99%